Bullous dermatosis suspected in an 8-month-old child in Guinea-Bissau - Valle del Barrio, Beatriz (Oxf Med Case Reports, 2019)
An 8-month-old child was admitted to a paediatric intensive care unit in Guinea-Bissau with severe blistering dermatosis. He was treated with broad spectrum antibiotics and dressings, without improvement. After 2 weeks, linear IgA bullous dermatosis was suspected. Owing to lack of dapsone, the child was treated with prednisolone and improved. To avoid corticosteroids side effects, 2 months after starting prednisolone we switched to colchicine, but the boy’s condition worsened for reasons of poor adherence, requiring intravenous corticosteroids and antibiotics. After complete resolution of the skin lesions, we continued with colchicine monotherapy, then changed to dapsone after 3 months. The child did not show any further signs of dermatosis, but his follow-up ended abruptly, because he did not return to the hospital. IgA bullous dermatosis is a challenging diagnosis in settings where pathological studies cannot be conducted. Multidisciplinary treatment is required and colchicine is a good option if dapsone is not available.